Automated post-processing for sheet metal component manufacturing. (May 2020) - Sehmi, Maninder; Christensen, Jesper; Bastien, Christophe; Wilson, Alexis; Kanarachos, Stratis
Highlights: Automation of Post-Processing of Topology Optimisation Results. Creation of semi-automated customisable optimisation refinement tool. Standalone topology optimisation post-processor. Refinement of topology optimised designs for sheet metal manufacturing. Abstract: Topology optimisation is an increasingly important process used in a variety of industries to improve the designs of manufacturable products. The higher reliance of optimisation software, used for instance in the automotive industry, highlights its importance for designing more efficient and refined mass-produced components. Post-processing of topology optimisation results (e.g. from variable density to manufacturable structures) does however remain a heavily heuristic process where the end-results (and consequently the "efficiency" of the optimised product) can vary significantly as a function of the individual designer/engineer. This "variation" coupled with the often-significant time associated with post-processing makes the use of topology optimisation prohibitive in certain instances. In this paper, a systematic and repeatable three-step approach to automated post-processing of topology optimisation results for sheet metal manufacturing of automotive components will be introduced. The method, which has been implemented into a software tool, is mesh independent and can handle topology optimisation results in binary as well as variable density formats. The software contains three main steps; namely geometry refinement, re-analysis and manufacturability check. The methodology and software utilise a stencil method, for which the principles are described here. The main objective from this is to generate repeatable refined interpretations of optimisation results. In addition to presenting the actual methodology and software, this paper also investigates different parameter variations; such as geometry update sequence, search radii, stencil shape and type and their influence on the generated post-processed result. Definition of algorithm parameters is provided, together with suggested user-defined settings to enable the derivation of consistent refinements of the topology results.